Digital transformation of school management by utilizing google sites - Dian Aprianto; Bambang Ismanto; Sophia Tri Satyawati; Landro Sette; Angelique Yulica Dosmaroha (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to develop a digital transformation of school management by utilizing Google Sites. The design of this research and development uses the Borg & Gall model which consists of ten steps. However, the researcher will only reach the fifth step, namely the main product trial. The subjects in this study were the principal, teachers, administrative staff, and parents of students at SD Kristen Lentera Ambarawa. Data collection techniques used observation, interviews, and documentation. Data was validated using source and technique triangulation techniques. Data analysis techniques used the Miles and Huberman Model. The products produced were the Google Sites website, model books and user guides. Research results: 1) The use of Google Sites can facilitate access to information for teachers, students, and parents, and strengthen the school's digital documentation system at SD Kristen Lentera Ambarawa. 2) Development of school management by utilizing Google sites with the results of content validity of management of 88.6%, while media validity was 92.5%, meeting the criteria of "very valid" or worthy of being tested. while the average trial of the Google Sites application for teachers, principals, and school stakeholders was 98%, so based on this, the development of digital transformation of school management by utilizing Google Sites at SD Kristen Lentera Ambarawa is in the very good category.